Gradual Stages of Word Adoption into Uzbek - Babadjanova Xadicha Kapal qizi (Zien Journals, 2021)
This article discusses the gradual stages of word adoption into the Uzbek language. In particular, structure and content of the words, such as garm, farsang, baxshish, daha were analyzed in terms of etymology and semantics
Keywords: Dictionary fund; word; borrowed word; substrate layer